2012
DOI: 10.1111/j.1744-7909.2012.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

ROP11 GTPase is a Negative Regulator of Multiple ABA Responses in Arabidopsis

Abstract: The phytohormone abscisic acid (ABA) plays crucial roles in plant development and plant responses to environmental stresses. Although ABA receptors and a minimal set of core molecular components have recently been discovered, understanding of the ABA signaling pathway is still far from complete. In this work, we characterized the function of ROP11, a member of the plant-specific ROP small GTPases family, in the ABA signaling process. ROP11 is preferentially expressed in guard cells in all plant organs with sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 35 publications
4
60
0
Order By: Relevance
“…In this study, we evaluated the drought resistance of 14 transgenic Arabidopsis-overexpressing PYLs driven by the constitutive 35S cauliflower mosaic virus (CaMV) promoter, the stress-inducible RD29A promoter, the guard cell-specific GC1 and ROP11 promoters (20,21), and the green tissue-specific ribulose bisphosphate carboxylase small subunit (RBCS) RBCS-1A promoter (22). We found that, relative to the WT and all other combinations, pRD29A::PYL9 transgenic Arabidopsis plants had both greater drought resistance and accelerated drought-or ABA-induced leaf senescence.…”
Section: Significancementioning
confidence: 99%
“…In this study, we evaluated the drought resistance of 14 transgenic Arabidopsis-overexpressing PYLs driven by the constitutive 35S cauliflower mosaic virus (CaMV) promoter, the stress-inducible RD29A promoter, the guard cell-specific GC1 and ROP11 promoters (20,21), and the green tissue-specific ribulose bisphosphate carboxylase small subunit (RBCS) RBCS-1A promoter (22). We found that, relative to the WT and all other combinations, pRD29A::PYL9 transgenic Arabidopsis plants had both greater drought resistance and accelerated drought-or ABA-induced leaf senescence.…”
Section: Significancementioning
confidence: 99%
“…Note. When this paper was under preparation, another group reported that ROP11 interacted with ABI1 and regulated ABA responses (34,35), although authors found that ABI1 interaction with ROP11 occurs when the regulatory domain of ABI1 is deleted (35). It seems likely that different cross-talk nodes are present in subcellular compartments, such as the nucleus and cytosol, where they link alternate signals to ABA.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, phenotypic analysis of rop10rop11 double mutant showed that they act in parallel pathways in ABA-mediated responses. Li et al ( 2012aLi et al ( , 2012b, using luciferase complementation imaging (LCI), Y2H assay, and co-immunoprecipitation assay, showed that activated ROP11 binds ABI1 (ABA insensitive), a PP2C phosphatase, and allows the downstream SnRKs to be activated, which further activate TFs and upregulate stress-related genes like RAD29 .…”
Section: Rac/rop Gtpases In Abiotic Stressmentioning
confidence: 99%